Closer to 90–90–90. The cascade of care after 10 years of ART scale‐up in rural Malawi: a population study. Issue 1 (15th February 2016) - Maman, David; Chilima, Benson; Masiku, Charles; Ayouba, Ahidjo; Masson, Sophie; Szumilin, Elisabeth; Peeters, Martine; Ford, Nathan; Heinzelmann, Annette; Riche, Benjamin; Etard, Jean‐François
Abstract : Introduction: The antiretroviral therapy (ART) programme supported by Médecins Sans Frontières in the rural Malawian district of Chiradzulu was one of the first in sub‐Saharan Africa to scale up ART delivery in 2002. After more than a decade of continuous involvement, we conducted a population survey to evaluate the cascade of care, including population viral load, in the district. Methods: A cross‐sectional household‐based survey was conducted between February and May 2013. Using a multistage cluster sampling method, we recruited all individuals aged 15 to 59 years living in 4125 randomly selected households. Each consenting individual was interviewed and tested for HIV at home. All participants who tested positive had their CD4 count and viral load measured. The LAg‐Avidity assay was used to distinguish recent from long‐term infections. Viral suppression was defined as a viral load below 1000 copies/mL. Results: Of 8271 individuals eligible for the study, 7269 agreed to participate and were tested for HIV (94.1% inclusion for women and 80.3% for men). Overall HIV prevalence and incidence were 17.0% (95% CI 16.1 to 17.9) and 0.39 new cases per 100 person‐years (95% CI 0.0 to 0.77), respectively. Coverage at the other steps along the HIV care cascade was as follows: 76.7% (95% CI 74.4 to 79.1) had been previously diagnosed, 71.2% (95% CI 68.6 to 73.6) were under care and 65.8% (95% CI 62.8 to 68.2) were receiving ART. Finally, the proportion of participants who were HIV positive with a viral load ≤1000 copies/mL reached 61.8% (95% CI 59.0 to 64.5). Conclusions: This study demonstrates that a high level of population viral suppression and low incidence can be achieved in high HIV prevalence and resource‐limited settings.